2014
DOI: 10.1289/ehp.1307151
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Concentrated Ambient PM 2.5 Increases Mouse Blood Pressure through Abnormal Activation of the Sympathetic Nervous System: A Role for Hypothalamic Inflammation

Abstract: Background: Exposure to particulate matter ≤ 2.5 μm in diameter (PM2.5) increases blood pressure (BP) in humans and animal models. Abnormal activation of the sympathetic nervous system may have a role in the acute BP response to PM2.5 exposure. The mechanisms responsible for sympathetic nervous system activation and its role in chronic sustenance of hypertension in response to PM2.5 exposure are currently unknown.Objectives: We investigated whether central nervous system inflammation may be implicated in chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
102
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 43 publications
12
102
1
3
Order By: Relevance
“…[8][9][10] Animal studies further implicated PM 2.5 as a stressor to the central nervous system that might induce a cascade of neuroendocrine responses. 11,12 These provocative findings warrant mechanistic investigations in humans.…”
mentioning
confidence: 98%
“…[8][9][10] Animal studies further implicated PM 2.5 as a stressor to the central nervous system that might induce a cascade of neuroendocrine responses. 11,12 These provocative findings warrant mechanistic investigations in humans.…”
mentioning
confidence: 98%
“…5J shows that CAP exposure did not impact the expression of SOCS3 in WT controls, but significantly increased its expression in KO mice, further supporting the central leptin resistance in CAP-exposed TNF/LT KO mice. CAP exposure has been shown to cause hypothalamic inflammation that may play a role in the pathogenesis of central leptin resistance (Ying et al, 2014). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Age-matched wildtype (C57BL/6J) mice were purchased from the Jackson Laboratories (Stock #000664) and were allowed to acclimate for two weeks in animal facilities at UMB before beginning inhalation exposure protocols. Animal exposure and the monitoring of exposure atmosphere and ambient aerosol were performed as previously described using a versatile aerosol concentration enrichment system that was modified for long-term exposures (Ying et al, 2014). Briefly, 10-week-old WT and KO mice were randomly grouped ( N = 7–8/group, male only) and subjected to filtered air (FA) or CAP exposure from October 2015 to March 2016.…”
Section: Methodsmentioning
confidence: 99%
“…In animal models, longer-term exposures elicit elevations in BP via sympathetic activation induced by hypothalamic inflammation and/or by endothelial dysfunction favouring vasoconstriction (e.g. rho kinase activation) [25,26]. Although we have shown that the inhalation of very high levels of airborne particles [20,24] can raise BP within hours, the fact that the pro-hypertensive response was delayed by a few days (which accords with many prior studies) [6] supports the contention that slower mechanistic pathways (e.g.…”
Section: Potential Mechanismsmentioning
confidence: 99%